2022
DOI: 10.4178/epih.e2023004
|View full text |Cite
|
Sign up to set email alerts
|

Parental concerns about COVID-19 vaccine safety and hesitancy in Korea: implications for vaccine communication

Abstract: M Yoo and H Lee conceived and designed the study. S Kim, S Seo and J Moon gathered, processed, cleaned and analysed the data. GY Kwon, JY Shin, SY Choi, and MJ Jeong worked on project administration and methodology. HK Cho and H Lee wrote the first draft of the manuscript followed by iterative revision with EH Choi, YJ Choe and MS You.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…The survey revealed that parents with a lower COVID-19 vaccine-related safety concerns had 37% lower odds of being high-hesitant than those with higher concern and those who delayed at least one shot of a recommended vaccine for their child were 2.33 times more likely to be high-hesitant. This finding is consistent with those observed in previously conducted surveys ( 49 , 51 ). Moreover, delayed of at least one shot of a recommended vaccine for their child underlined the need of targeted activities through a better parent-physician communication that may be crucial toward enhancing vaccination coverage.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The survey revealed that parents with a lower COVID-19 vaccine-related safety concerns had 37% lower odds of being high-hesitant than those with higher concern and those who delayed at least one shot of a recommended vaccine for their child were 2.33 times more likely to be high-hesitant. This finding is consistent with those observed in previously conducted surveys ( 49 , 51 ). Moreover, delayed of at least one shot of a recommended vaccine for their child underlined the need of targeted activities through a better parent-physician communication that may be crucial toward enhancing vaccination coverage.…”
Section: Discussionsupporting
confidence: 94%
“…Parents who had these positive attitudes were 2.58 and 1.66 times more willing to vaccinate their child when compared with parents who had unfavorable attitudes. This finding is consistent with those of several recently conducted studies showing that parents’ opinions about the efficacy of the vaccines in general have a significant impact in vaccine acceptance ( 13 , 15 , 18 , 23 , 49 , 50 ). Therefore, public health education programs for parents with a negative attitude toward the utility of the COVID-19 vaccine would result in a high vaccine acceptance with an increase in the uptake.…”
Section: Discussionsupporting
confidence: 92%
“…Post-COVID-19 pandemic studies have frequently pointed to vaccine safety concerns as a primary factor in vaccination hesitancy. 29 , 30 , 35–37 Interestingly, when comparing this factor with individuals who received either the influenza vaccine alone or the co-administration of influenza and COVID-19 vaccines, the results differed. The perceived barriers, including concerns about adverse reactions and safety issues, were not significant in these groups.…”
Section: Discussionmentioning
confidence: 97%
“…[ 17 18 ] In a survey conducted by Cho et al . [ 19 ] in August 2021, approximately 56.4% (575/1,019) were willing to vaccinate their children against COVID-19 in Korea.…”
Section: Discussionmentioning
confidence: 99%